ZEB2 drives immature T-cell lymphoblastic leukaemia development via enhanced tumour-initiating potential and IL-7 receptor signalling - Goossens, Steven (Nat Commun, 2015)
Early T-cell precursor leukaemia (ETP-ALL) is a high-risk subtype of human leukaemia that is poorly understood at the molecular level. Here we report translocations targeting the zinc finger E-box-binding transcription factor ZEB2 as a recurrent genetic lesion in immature/ETP-ALL. Using a conditional gain-of-function mouse model, we demonstrate that sustained Zeb2 expression initiates T-cell leukaemia. Moreover, Zeb2-driven mouse leukaemia exhibit some features of the human immature/ETP-ALL gene expression signature, as well as an enhanced leukaemia-initiation potential and activated Janus kinase (JAK)/signal transducers and activators of transcription (STAT) signalling through transcriptional activation of IL7R. This study reveals ZEB2 as an oncogene in the biology of immature/ETP-ALL and paves the way towards pre-clinical studies of novel compounds for the treatment of this aggressive subtype of human T-ALL using our Zeb2-driven mouse model.